2018
DOI: 10.1007/s11010-018-3435-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy

Abstract: The critical role of the intrarenal renin-angiotensin system (RAS) in the development of kidney disease has been well demonstrated in animal and cell-culture experiments, but evidence from human kidney tissues is lacking. In this study, we screened 438 patients with IgA nephropathy (IgAN) and analyzed their clinical characteristics. Renal biopsy revealed the expression of angiotensin II type 1 receptor (AT1R), angiotensin II type 2 receptor (AT2R), and MAS receptor (MASR) in the tissues of 260 patients not tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Several groups have reported that RAS component expression in human kidney biopsies correlates with the presence and severity of the underlying kidney disease ( Lai et al, 1998 ; Del Prete et al, 2003 ; Mezzano et al, 2003 ; Konoshita et al, 2006 ; Kobori et al, 2007a ; Takamatsu et al, 2008 ; Ohashi et al, 2017 ; Zhang et al, 2019 ). In patients with mixed etiology kidney disease, RAS component mRNA levels were upregulated in glomeruli and tubules compared with controls ( Lai et al, 1998 ).…”
Section: Intrarenal Ras and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have reported that RAS component expression in human kidney biopsies correlates with the presence and severity of the underlying kidney disease ( Lai et al, 1998 ; Del Prete et al, 2003 ; Mezzano et al, 2003 ; Konoshita et al, 2006 ; Kobori et al, 2007a ; Takamatsu et al, 2008 ; Ohashi et al, 2017 ; Zhang et al, 2019 ). In patients with mixed etiology kidney disease, RAS component mRNA levels were upregulated in glomeruli and tubules compared with controls ( Lai et al, 1998 ).…”
Section: Intrarenal Ras and Diseasementioning
confidence: 99%
“…Greater AGT and Ang II immunoreactivity was also observed in glomeruli from pediatric patients with IgA nephropathy ( Takamatsu et al, 2008 ). Expression of the AT 1 receptor in patients with IgA nephropathy is related to disease severity and reduced by RAS inhibition ( Zhang et al, 2019 ).…”
Section: Intrarenal Ras and Diseasementioning
confidence: 99%
“…25 Our previous research also found that MAR receptor expression levels were significantly higher in the group of mesangial hypercellularity. 26 Currently, we believe that the local MAS receptor in the kidney is a protective receptor, and its expression is increased in the case of kidney damage.…”
Section: Discussionmentioning
confidence: 99%
“…The renin-angiotensin system (RAS) plays an important role in the pathophysiology of renal diseases. IgAN is characterized by local activation of the RAS and upregulated expression of the angiotensin receptor type 1 (AT1R) (3)(4)(5). New components of the RAS have been identified recently, including angiotensin (Ang)-(1-7), Mas receptor (MasR), Ang-(1-9) and alamandine (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Almost 30% of patients require dialysis or transplant within 20 years after diagnosis. Mesangial cell hyperplasia and mesangial matrix accumulation (i.e., mesangial lesions) are the main pathological lesions of IgAN, and directly cause glomerulosclerosis and, subsequently, renal failure ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%